2015
DOI: 10.1017/s0021859615000933
|View full text |Cite
|
Sign up to set email alerts
|

Statistical modelling of grapevine phenology in Portuguese wine regions: observed trends and climate change projections

Abstract: SUMMARYPhenological models are considered key tools for the short-term planning of viticultural activities and long-term impact assessment of climate change. In the present study, statistical phenological models were developed for budburst (BUD), flowering (FLO) and veraison (VER) of 16 grapevine varieties (autochthonous and international) from the Portuguese wine-making regions of Douro, Lisbon and Vinhos Verdes. For model calibration, monthly averages of daily minimum (Tmin), maximum (Tmax) and mean (Tmean) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
75
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(85 citation statements)
references
References 61 publications
9
75
0
1
Order By: Relevance
“…Smaller changes are expected for other regions in western/central Europe, such as northern France and Germany. These outcomes are in general agreement with previous studies projecting future advances in grapevine phenological timings throughout Europe (García De Cortázar‐Atauri et al ., ; Donatelli et al ., ), Germany (Neumann & Matzarakis, ), France (Duchene et al ., ; Cuccia et al ., ), Italy (Caffarra & Eccel, ) and Portugal (Fraga et al ., 2016b). Nonetheless, the phenology submodel used in STICS does not take into account very high temperature effect (Wang and Engel model), which may result in biases in very hot regions (Cuccia et al ., ).…”
Section: Resultsmentioning
confidence: 99%
“…Smaller changes are expected for other regions in western/central Europe, such as northern France and Germany. These outcomes are in general agreement with previous studies projecting future advances in grapevine phenological timings throughout Europe (García De Cortázar‐Atauri et al ., ; Donatelli et al ., ), Germany (Neumann & Matzarakis, ), France (Duchene et al ., ; Cuccia et al ., ), Italy (Caffarra & Eccel, ) and Portugal (Fraga et al ., 2016b). Nonetheless, the phenology submodel used in STICS does not take into account very high temperature effect (Wang and Engel model), which may result in biases in very hot regions (Cuccia et al ., ).…”
Section: Resultsmentioning
confidence: 99%
“…As temperatures are a major driver of the grapevine development stages (Parker et al, 2013), significant warmings are expected to lead to earlier onsets (Bock et al, 2011;Chuine et al, 2004;Dalla Marta et al, 2010;Daux et al, 2011;Jones et al, 2005a;Molitor et al, 2014;Sadras and Petrie, 2011;Webb et al, 2011). Recent studies for Portugal isolated future projections for the phenological stages of 16 native varieties under RCP4.5 and 8.5 (Fraga et al, 2015;Fraga et al, 2016c;Malheiro et al, 2013). The results hint at earlier onsets of 2-5 days for budburst and flowering, and of 7-15 days for veraison until 2070, depending on the selected future scenario and variety.…”
Section: Impacts On Phenologymentioning
confidence: 99%
“…Moriondo et al (2011) suggested possible negative effects of temperature increase on wine quality in the Mediterranean area (particularly Italy). The recorded advance in phenological timing (Caffarra and Eccel, 2011;Tomasi et al, 2011;Fraga et al, 2015) is a clear warning against a change in the match between a variety and its longlived growing context, questioning the subsistence of the balance between the ripening process and the meteorological conditions occurring in the relevant period (Mullins et al, 1992). The action of meteorological drivers on physiological development may also affect yield (Bindi et al, 1996;Duchêne and Schneider, 2005;Webb et al, 2008), due to an expected higher, unsatisfied water demand in summer, and to a shorter ripening period.…”
Section: Introductionmentioning
confidence: 99%